ANALISIS TINGKAT KEPUASAN KERJA KARYAWAN DALAM MENGELOLA WEDDING EVENT DI THE ROYAL SANTRIAN, TANJUNG BENOA-BALI - Chairini, Alda; Indrawati, Yayu; Sasrawan Mananda, I GPB. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 1 No 1 (2013): Jurnal IPTA (December 2013)DO - 10.24843/IPTA.2013.v01.i01.p01, 2013)
This research aims to determine the employee satisfaction in wedding events at The Royal Santrian and results can be used to improve and optimizing their productivity. The qualitative and quantitative analysis technique are used in this research, and the result will be explained using quantitative description with likert scale approach. The employee satisfaction is divided into five indicators, such as compensation, promotion, physical environment, non-physical environment, and job characteristic, every indicator include two questions and the total is ten questions. The total score is 103.226 which means that the employees are satisfied while working for wedding event at The Royal Santrian.
Keywords: Employee Satisfaction, Wedding Event